A Novel Approach for Heart Disease Classification using Feature Selection - UmaDevi, R; Azhakarsamy, Raynuka; Sathiaseelan, J.G.R (International Journal of Computer Sciences and Engineering, 2025)
Heart disease is predicted by classification technique. The data mining tool WEKA has been utilized for implementing J48 classifier. Proposed work is framed with a specific end goal to enhance the execution of models. For improving the classification accuracy J48 is combined with Bagging and Feature Selection. Trial results demonstrated a critical change over in the current J48 classifier. This approach enhances the classification accuracy and reduces computational time